2014
DOI: 10.5951/jresematheduc.45.4.0419
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Teachers' Mathematical Content and Pedagogical Knowledge, Teachers' Perceptions, and Student Achievement

Abstract: This study of early-career teachers identified a significant relationship between upper-elementary teachers' mathematical content knowledge and their students' mathematics achievement, after controlling for student- and teacher-level characteristics. Findings provide evidence of the relevance of teacher knowledge and perceptions for teacher preparation and professional development programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(72 citation statements)
references
References 37 publications
1
67
0
4
Order By: Relevance
“…Beliefs are typically viewed as "psychologically held understanding, premises, or propositions about the world that are felt to be true" (Richardson, 1996, p. 102). As Campbell et al (2014) write, ". .…”
Section: Teacher Beliefs About Swds Ability and Instructional Needs Imentioning
confidence: 99%
“…Beliefs are typically viewed as "psychologically held understanding, premises, or propositions about the world that are felt to be true" (Richardson, 1996, p. 102). As Campbell et al (2014) write, ". .…”
Section: Teacher Beliefs About Swds Ability and Instructional Needs Imentioning
confidence: 99%
“…Sebaliknya, jika semakin rendah tingkat PCK guru matematika, maka prestasi belajar matematika siswa juga akan semakin rendah. Temuan ini sejalan dengan hasil penelitian dari Campbell et al (2014) dan Olfos et al (2014) yang menunjukkan terdapat hubungan signifikan antara tingkat PCK guru dan prestasi belajar siswa. Bahkan penelitian yang dilakukan oleh Baumert et al (2010) huan pokok yang menjadi penuntun bagi guru dalam mengambil keputusan ataupun mengambil tindakan dalam proses pembelajaran di kelas (Atay et al, 2010).…”
Section: Pembahasanunclassified
“…Researchers have considered the relationship between teacher TPACK and students' outcomes from various angles and have reported opposing findings. For example, Fauth et al (2019), Campbell et al (2014), and Agyei and Keengwe (2012) showed that teachers' TPACK is related to students' achievement. Conversely, other researchers (for instance, Farrell and Hamed, 2017) found that there was no relationship between teachers' TPACK and students' achievements.…”
Section: Open Accessmentioning
confidence: 99%